Optimizing epoxy curing in fibre reinforced polymers - Lim, Cecilia Meng Li (2016)
Fibre reinforced polymer (FRP) has gained popularity over the years in numerous applications, including the use as structural reinforcements due to its high strength and toughness. Hand lay-up method is most commonly used for the application of FRP for structural reinforcements. However, this method is time consuming and labour intensive. This project seeks to improve the efficiency of applying FRP through the development of a semi-cured, tacky FRP roll which could ease the on-site application of FRP. In this report, two epoxy systems were explored, an ambient cure epoxy system and an ultraviolet cure epoxy system. The hardener content in the ambient cure epoxy was varied, and the effect on the degree and cure and tack was studied. Quantification of degree of cure was done with the use of Differential Scanning Calorimetry while mechanical testing was used to quantify the tack of the system with an improvised probe tack test. The intensity of ultraviolet light used to cure the ultraviolet cure epoxy was varied to understand the effect of intensity on cure, and the extent of cure was studied with the use of Differential Photocalorimetry. A reduction in the hardener content for the ambient cure epoxy was found to decrease the degree of cure and delay the onset of dry-to-touch time, a state where the epoxy surface is no longer tacky when touched. As for the ultraviolet cure epoxy, an inverse relationship between intensity and cure time was identified, and the dark curing properties of the epoxy was found to offer potential to overcome the issue of blockage of light due to the fibres in the FRP. These studies have allowed a better understanding on the potential of these systems in the application, and recommendations on future work and possible explorations are provided for the development of the FRP roll.